Combined antioxidant (β-carotene, α-tocopherol and ascorbic acid) supplementation increases the levels of lung retinoic acid and inhibits the activation of mitogen-activated protein kinase in the ferret lung cancer model - Yuri Kim (2018)
Interactions among β-carotene (BC), α-tocopherol (AT) and ascorbic acid (AA) led to the hypothesis that using a combination of these antioxidants could be more beneficial than using a single antioxidant alone, particularly against smoke-related lung cancer. In this investigation, we have conducted an animal study to determine whether combined BC, AT and AA supplementation (AOX) protects against 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung carcinogenesis in smoke-exposed (SM) ferrets. Ferrets were treated for 6 months in the following four groups: (i) control, (ii) SM + NNK, (iii) AOX and (iv) SM + NNK + AOX. Results showed that the combined AOX supplementation (i) prevented the SM + NNK-decreased lung concentrations of retinoic acid (RA) and BC; (ii) inhibited the SM + NNK-induced phosphorylation of Jun N-terminal kinase (JNK), extracellular-signal-regulated protein kinase (ERK) and proliferating cellular nuclear antigen proteins in the lungs of ferrets; and (iii) blocked the SM + NNK-induced up-regulation of total p53 and Bax proteins, as well as phosphorylated p53 in the lungs of ferrets. In addition, there were no lesions observed in the lung tissue of ferrets in the control and/or the AOX groups after 6 months of intervention, but combined AOX supplementation resulted in a trend toward lower incidence of both preneoplastic lung lesions and lung tumor formation in SM + NNK + AOX group of ferrets, as compared with the SM + NNK group alone. These data indicate that combined AOX supplementation could be a useful chemopreventive strategy against lung carcinogenesis through maintaining normal tissue levels of RA and inhibiting the activation of mitogen-activated protein kinase pathways, cell proliferation and phosphorylation of p53. © 2006 Oxford University Press.